Analysis of Siphon String Application to Optimize Gas Lift Injection - Sofani Muflih; Silvya Dewi Rahmawati (Journal of Earth Energy Science, Engineering, and Technology, 2021)
B-X well is an oil producing well at Bravo field in Natuna offshore area, which was completed at IBS zone using 5-1/2 inch tubing size. However, after several years of production period, the well’s production rate decreased due to reservoir depletion, and experienced gas lift performance problem indicated by unstable flowing condition (slugging flow). In year 2020, Siphon String installation is applied to the well in order to give deeper point of gas lift injection and better well’s production. The additional advantage by having smaller tubing size (insert tubing) is to reduce the slugging flow condition. The analysis of this siphon string installation at the B-X well, technically will be performed by evaluating gas lift performance and the flow regime inside the tubing using a Well Model simulator. The simulation was developed based on the real well condition. Several sensitivity analysis were done through several cases such as: variation in depth of gas lift point of injection, and the length of the siphon string. The simulation was required to evaluate the effectiveness of the existing installation, and to give better recommendation for the other well that has the same problem.  The result indicates that the depth of the current siphon string installation has been providing the optimum production rate, while the slugging flow condition will still be occurred at any given scenario of the siphon string depth due to the very low of well’s productivity. The similar procedure and evaluation can be implemented to other oil wells using gas lift injection located either in offshore or onshore field.  Keywords: Production Optimization, Siphon String, Flow Regime